Effectiveness of protected areas in containing the loss of Peruvian Amazonian forests - Rojas Briceño, Nilton B.; Cajas Bravo, Verónica; Pasquel Cajas, Alexander; Guzman Valqui, Betty Karina; Silva López, Jhonsy O.; Veneros, Jaris; García, Ligia (Elsevier, 2025)
Peruvian Amazonian Forests (PAF), vital for biodiversity, climate, and human well-being, lost 2.92M ha during 2001-2022, mainly due to anthropogenic activities. This prompted strategies to conserve and protect the PAF, such as land use and natural resource restrictions, with natural protected areas (NPAs) being the main strategy. This study evaluated the effectiveness of 41 NPAs in containing deforestation in the PAF by analyzing national spatial data. An Effectiveness Index (EI) was constructed by adding five standardized parameters: (1) the percentage of deforested area (DA%) and (2) its annual rate of change (DAr) between 2000 and 2022 inside each NPA, (3) the difference in DAr between NPAs and their surrounding areas, (4) their corresponding ecoregions, and (5) the entire PAF. In 2000, the DA% was 7.15% of the PAF, increasing to 10.88% in 2022. NPAs showed lower DAr than their surrounding areas and ecoregions, except for five NPAs. Of the 41 NPAs, nine were non-effective (EI≤3), 31 moderately effective (3<EI<4), and only one effective (EI≥4). Indirect-use NPAs (strict with integral protection) were slightly more effective than direct-use NPAs (where sustainable use is allowed). Among national categories, the 11 National Parks, equivalent to IUCN Category II, had the highest average EI (3.414). In general, NPAs have shown moderate effective in containing deforestation, and require risk-specific mitigation strategies, especially in NPAs with low DA% but high DAr. Finally, a quantitative and systematic assessment tool is provided, which can improve the formulation of strategies to mitigate deforestation and preserve crucial ecosystem services in PAF.